Surface characteristics and bioactivity of zirconia (Y-TZP) with different surface treatments - Gayathree Alagiriswamy; Chitra Shankar Krishnan; Hariharan Ramakrishnan; Sampath Kumar Jayakrishnakumar; Vallabh Mahadevan; Nagarasampatti Sivaprakasam Azhagarasan (Wolters Kluwer Medknow Publications, 2020)
Background: Zirconia being a bio-inert material needs to be surface treated to render it more bioactive and enhance its osseointegration potential. However, bioactivity studies focusing on the ability of sandblasting and ultraviolet photofunctionalization (UVP) surface treatments in inducing apatite precipitation using simulated body fluid (SBF) are lacking. Aim: The aim of the study was to comparatively evaluate the effect of two different surface treatments-sandblasting with 50 µm alumina and UVP with ultraviolet C (UVC) light on the bioactivity of zirconia. Materials and Methods: A total of 33 discs with dimensions 10 mm × 2 mm were obtained from zirconia blanks (Amann Girrbach, Koblach, Austria) and randomly divided into three groups (n = 11), namely Group I (untreated), Group II (sandblasted), and Group III (UVP). Surface characteristics of representative test samples were analyzed using X-ray diffraction (XRD), atomic force microscopy (AFM), contact angle goniometry, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX), to assess type of crystal phase of zirconia, surface roughness, wettability, surface topography, and elemental composition, respectively. SBF was prepared and calcium content in SBF (Ca-SBF) was determined using inductively coupled plasma mass spectrometry (ICP-MS). Results: Data were analyzed by one-way analysis of variance (ANOVA), post hoc Tukey honestly significant difference (HSD), and Student's t test for statistical significance (P < 0.05, significant; P < 0.01, highly significant). Surface characteristics analyses revealed that XRD showed predominant tetragonal (t) zirconia crystal phase for all test groups. Mean surface roughness (Sa) of Group I was 41.83 nm, and it was significantly lesser than that of Group II (115.65 nm) and Group III (102.43 nm). Mean contact angles were 98.26°, 86.77°, and 68.03° for Groups I, II, and III, respectively, and these differences were highly significant. Mean pre-immersion Ca content in SBF was found to be 159 mg/L. Mean post-immersion Ca content was 70.10, 60.80, and 56.20 mg/L for Groups I, II, and III, respectively. Significant differences were found between Group I as compared to both Groups II and III. Bioactivity of Group III was marginally, but insignificantly higher with respect to Group II. Groups II and III were insignificant with respect to each other. Post-immersion XRD revealed predominant "t" phase, and SEM-EDX revealed well-formed, abundant calcium apatite layer on the treated samples as compared to that on untreated sample and an increasing Ca/P ratio from 1.15, 1.79 to 2.08, respectively from Group I to Group III. Conclusion: Within the limitations of this study, both sandblasting and UVP significantly and similarly improved bioactivity of zirconia as compared to the untreated samples, which was corroborated by the SEM-EDX results.